2014
DOI: 10.1186/2052-336x-12-57
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of a prospective remediation method for PCB-contaminated paint

Abstract: BackgroundPaint laden with polychlorinated biphenyls (PCBs) often acts as a point source for environmental contamination. It is advantageous to address contaminated paint before the PCBs transport to surrounding media; however, current disposal methods of painted material introduce a variety of complications. Previous work demonstrates that PCBs can be broken down at ambient temperatures and pressures through a degradation process involving magnesium metal and acidified ethanol. This report is an extension of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…BTEX compounds are classified as major environmental pollutants on the Environmental Protection Agency (EPA) list of priority pollutants with high frequencies of occurrence (Farhadian et al 2008) which may be lethal and persistent in terrestrial and aquatic environments. The volatile organic compounds (VOCs) like ethylbenze, n-hexane, and xylene in the oil-based paints, on the other hand, are considered to be harmful to the environment, especially for the people who work with them on a regular basis (Saitta et al 2014). The exposure to VOCs has been related to organic solvent syndrome (Spurgeon 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTEX compounds are classified as major environmental pollutants on the Environmental Protection Agency (EPA) list of priority pollutants with high frequencies of occurrence (Farhadian et al 2008) which may be lethal and persistent in terrestrial and aquatic environments. The volatile organic compounds (VOCs) like ethylbenze, n-hexane, and xylene in the oil-based paints, on the other hand, are considered to be harmful to the environment, especially for the people who work with them on a regular basis (Saitta et al 2014). The exposure to VOCs has been related to organic solvent syndrome (Spurgeon 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biological removal (bioremediation) treatment technology has turned out to be a favorable alternative because it produces no toxic end products and is cost-effective (Mohsenzadeh et al 2012). Recently, Saitta et al (2014) reported a potential remediation method for PCBcontaminated paint under laboratory conditions based on non-metallic treatment system (NMTS). The methods like NMTS, in addition to bioremediation, could facilitate complete remediation of the oil-based-paint-contaminated ecosystems through cost-effective and environmentfriendly processes.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the PCB values in the treatment system continually increased as the concentration in the paint remained steady it is possible that PCBs from surrounding areas, including the concrete, were drawn into the treatment system. Spot concrete samples taken before and after the treatment indicated that the BTS and NMTS removed residual PCBs in the underlying material, a phenomenon seen in similar studies on remediating porous painted surfaces (Legron-Rodriguez, 2013;Saitta et al, 2014).…”
Section: Treatment Of Painted Concrete In Press Houses a And Bmentioning
confidence: 82%
“…The treatment system was then removed and discarded, minimizing environmental exposure. The first formulation, and the foundation for the subsequent formulations, was the Non-Metal Treatment System (NMTS) comprised of solvent, a paint softener, and bulking agents (Saitta et al, 2014). The NMTS was formulated to extract PCBs from a painted surface and to act as a delivery system for metal reaction components.…”
Section: Introduction To Treatment Technologymentioning
confidence: 99%
“…To determine the concentrations of naphthalene, cumulative content of PAH compounds (anthracene, acenaphthene, asenaphthylene, bentz(a)anthracene, benzo(a)pyrene, benzo(b)fluoranthene, benzo(g,h,i)perylene, benzo(k)fluoranthene, dibenzo(a,h)anthracene, phenanthrene, fluoranthene, fluorene, indeno(1,2,3-cd)pyrene, chrysene, naphthalene and pyrene), cumulative content of PCB compounds (congeners 28, 52, 101, 118, 138, 153 and 180) as well as the petroleum hydrocarbons (C 10 -C 40 ) in the traction sand, the in-house method based on standards SFS-ISO 18287 for PAHs (Paxal 2012), USEPA 3665A for PCBs (Saitta et al 2014) and SFS-EN ISO 16703 for petroleum hydrocarbons (C 10 -C 40 ) (Paxal 2012) were used.…”
Section: Determination Of the Naphthalene Pah Pcb And Petroleum Hydmentioning
confidence: 99%